FEATURES OF ULTRASTRUCTURAL LONGTERM CHANGES IN THE PULMONARY RESPIRATORY TRACT OF RATS FOLLOWING THE THERMAL INJURY WHEN CORRECTED BY COLLOIDAL HYPEROSMOLAR INFUSION SOLUTION HAES-LX-5% - Макарова, О.І.; Чайковський, Ю.Б. (World of Medicine and Biology, 2014)
Treatment of thermal burns and their consequences is one of the topical problems in modern medicine. Pulmonary lesions have one of the leading positions among visceral manifestations of thermal injury. Recently low-molecular solutions have been widely used for rapid restoration of circulating blood volume and normalisation of electrolyte composition since hyperosmolarity causes transfer of fluid from the intercellular sector into the bloodstream, thereby improving microcirculation and tissue perfusion. A novel locally manufactured infusion solution HAES-LX-5% has similar effect. However neither clinical indicators of a thermal injury, nor the ultrastructural changes occurring in the respiratory system of rat in the process of its correction by infusion of colloid-hyperosmolar solutions have been specifically studied so far. The aim of the study was to investigate the longterm features of ultrastructural pulmonary changes in the rats after thermal injury and its correction by colloid hyperosmolar solution infusion HAES-LX-5%. Studies were carried out on Wistar mature white male rats weighing 160-180 g in the remote period after thermal injury (after 14, 21 and 30 days). All animals were subjected to thermal injury by applying four copper plates (two on each side of the body) previously held for six minutes in water at a constant temperature of 100 º C. The total area of burned skin was 21-23% when exposed for 10 sec, which was sufficient for the formation of the II-III degree burn and development of a moderate-to-severe shock. Burns, catheterization of the main vessels and decapitation were performed under intravenous anesthesia by propofol, 60 mg/kg of animal weight. Solution for correction has been infused for 6.5 min. at a dosage of 10 ml / kg of weight into the inferior vena cava after aseptic catheterization via the femoral vein. The first administration was performed 1 hour after the simulation of pathological condition, the subsequent infusions were performed once a day within the first 7 days. The animals were divided into several groups: the first group - rats without the burn, which were infused with 0.9% solution of NaCl; the second group - rats without burn infused with HAES-LX-5% solution; the third group - rats with skin burns, which were infused with solution of NaCl; the fourth group - rats with skin burns administered with solution HAES-LX-5%. Ultrastructural changes in the rat lungs were studied in the electron microscope TEM 125K. The changes revealed in the pulmonary blood microvessels of rats belonging to the fourth group were less pronounced than those in the rat lungs of the third group within a similar period of observation. The level of destructive and degenerative changes in the pulmonary tissues, as well as interstitial and alveolar edema, damage of respiratory epithelium and endothelium, secretion disorders of surfactant were much less pronounced in rats which were infused with solution HAES-LX-5% during the first 7 days after burn injury, than in rats after burn injury treated with 0.9% solution of NaCl for the same period of observation. Signs of reparative regeneration of cells and marked hypertrophy and hyperplasia of fibroblasts, increased number of elastic and collagen fibers in the alveolar septa were observed in the respiratory epithelium and endothelium of the fourth group of rats after 21 days of thermal injury to the skin. Signs of respiratory epithelial regeneration, alternating with the undamaged areas in the basal plate, hyperplasia and hypertrophy of collagen fibers were observed in rats, which were infused with solution HAES-LX-5% 30 days after burn injury to the skin.